The Small Group Discussion Method’s Effectivity for Improving the Students of Tenth-Grade Vocational High School 7 Semarang’s Speaking Ability: Small Group Discussion Method, Improve, Students’ Speaking Ability - Anwar, Yasinta; Setyaji, Arso; Ambarini, Ririn (Universitas PGRI Adi Buana Surabaya, 2023)
Many Indonesian students find it difficult to master English as a second language. One of the essential skills that must be mastered is speaking skill. People who like English must concerted effort to improve their English language skills. In teaching and learning, the teacher has a big responsibility. Teachers must master learning strategies to solve problems faced by the students and help them comprehend their speaking skills to achieve the goal of learning. This research uses experimental methodology to examine the effect of the small-group discussion method on students' ability to communicate verbally. The researchers applied a pre-experimental strategy, which included a pre-test before providing the chosen treatment. A post-test was given to complete the data collection after the treatments. The researchers used thirty-six students from SMK N 7 Semarang as a sample in this research. The research's findings indicates that the post-test score outperformed the pre-test score. On the other hand, at the significant level of 0,05, the t-score result is greater than the t-table. As a result, we can decide from the data analysis that the Alternative Hypothesis (Ha) is acceptable whereas the Null Hypothesis (Ho) is unacceptable. In accordance with the findings, conducting small group discussions as a teaching strategy significantly improves students' speaking abilities. As a result, it is suggested that English teachers offer this method as an attempt.